Qur'anic Values in the Luberan Tradition: Strengthening Religious Moderation Based on Local Wisdom - Albab, Ulul; Riandita, Lilik; Mutammam, Mutammam; Fanany, Rebecca; Ana, Nurlaila; Ta'rifin, Ahmad (Dialogia, 2023)
This study examines the harmony of the "Luberan" tradition in implementing the Qur'anic moderation religious values. This study uses a qualitative method of the field research approach. This analysis shows that; 1) The Luberan tradition applies the four parameters of religious moderation compiled by the Director General of Islamic Education, Kemang, Republic of Indonesia. First, the Luberan tradition plays a role in strengthening nationalism, which is illustrated through the poem Sekar Gendhing Asmaradana as a Javanese song with the theme of love for the motherland, cultural preservation, and activities to protect the environment as a form of implementing its contents. QS. Al Qashash: 85 and QS. An-Nisa': 66. Second, tolerance education in Luberan culture can be seen through the interaction between Muslim and non-Muslim residents in organizing events, the habit of exchanging food, and giving each other. Third, a study on the theme of peaceful Islam shows the integration of QS al-mumtahinah verse 8 as an anti-radicalism and anti-violence educational model. 2) Cultural practices in strengthening the value of religious moderation are taught from generation to generation through religious rituals and mysticism in Luberan culture. This research contributes to finding the concept of strengthening the values of culture-based religious moderation. In addition, this research can also be used as a basis for the Ministry of Religion to integrate cultural practices as a vehicle for moderation in religion.